Cellular and metabolic approaches to investigate the effects of graphene and graphene oxide in the fungi Aspergillus flavus and Aspergillus niger. (March 2019) - Nguyen, Hang Ngoc; Chaves-Lopez, Clemencia; Oliveira, Rodrigo Cardoso; Paparella, Antonello; Rodrigues, Debora F.
Abstract: A combination of approaches, including volatile organic compound (VOC) metabolomics, enzymatic activity and morphological investigations, are employed to provide insights on the toxic interactions among carbon-based nanomaterials and fungi. The model fungi investigated are Aspergillus niger and Aspergillus flavus. Their exposure to graphene (G) and graphene oxide (GO) presents 62% reduction in biomass and abnormal hyphae aspect. The stress response of these microorganisms in the presence of these nanomaterials is further determined by overall cell changes through apoptosis analyses and production of reactive oxygen species (ROS) by the fungal hyphae. The ROS production by these microorganisms exposed to the nanomaterials confirms cellular oxidative stress, which explains the apoptotic-like cell death observed in the presence of the nanomaterials. This fungal response is also linked to lower production of several important enzymes involved in the catabolism of nutrients for cell growth, such as acid phosphatase, Naphthol-ASBI phosphohydrolase, β-glucosidase and β-galactosidase. The presence of these nanomaterials also triggers changes in the production of VOC by the fungi. These changes are indicative of stress conditions since these compounds have significant roles in fungal metabolism. Overall, A. niger was more sensitive to GO and A. flavus was more sensitive to G. Graphical abstract: Image 1